Influence of chromatin compaction on simulated early radiation‐induced DNA damage using Geant4‐DNA. Issue 3 (14th February 2019) - Tang, N.; Bueno, M.; Meylan, S.; Incerti, S.; Tran, H. N.; Vaurijoux, A.; Gruel, G.; Villagrasa, C.
Abstract : Purpose: In this work, we present simulated double‐strand breaks (DSBs) obtained for two human cell nucleus geometries. The first cell nucleus represents fibroblasts, filled with DNA molecules in different compaction forms: heterochromatin or euchromatin only. The second one represents an endothelial cell nucleus, either filled with heterochromatin only or with a uniform distribution of 48% of heterochromatin and 52% of euchromatin, obtained from measurements carried out at IRSN. Protons and alpha particles of different energies were used as projectiles. Each cell nucleus model includes a multi‐scale description of the DNA target from the molecular level to the whole human genome representation. Methods: The cell nucleus models were generated using an extended version of the DnaFabric software in which a new model of euchromatin was implemented in addition to the existing model of heterochromatin. Thus, each nucleus model contains the complete human genome (a total of 6 Gbp) in the G0/G1 phase of the cycle, filled with a continuous chromatin fiber per chromosome that can take into account the heterochromatin and the euchromatin compaction. These geometries were then exported to a simulation chain using the Monte Carlo toolkit Geant4‐DNA to perform computations of the physical, physicochemical, and chemical stages, in order to evaluate the influence of chromatin compaction on DSB induction and the contribution of direct and indirect damage, as well as DSB complexity. Results: More direct damage and less indirect damage were observed in the heterochromatin than in the euchromatin. Nevertheless, no difference in terms of DSB complexity was observed between those formed in the heterochromatin or the euchromatin models. Yields of DSB/Gy/Gbp show an increase when both heterochromatin and euchromatin models are taken into account, compared to when only heterochromatin is considered. Conclusions: The results presented indicate that the chromatin compaction decreases DNA damage generated by ionizing radiation and thus, DNA compaction should be considered for the simulation of DNA repair and other cellular outcomes.